2014
DOI: 10.1089/cbr.2013.1531
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Imaging of212Pb-TCMC-Trastuzumab After Intraperitoneal Administration in Ovarian Cancer Patients

Abstract: Purpose: Study distribution, pharmacokinetics, and safety of intraperitoneal (IP) 212 Pb-TCMC-trastuzumab in patients with HER-2-expressing malignancy. Experimental Design: IP 212 Pb-TCMC-trastuzumab was delivered, after 4 mg/kg intravenous (IV) trastuzumab, to 3 patients with HER-2-expressing cancer who had failed standard therapies. Patients were monitored for toxicity and pharmacokinetics/dosimetry parameters. Results: Imaging studies after 0.2 mCi/m 2 (7.4 MBq/m 2 ) show little redistribution out of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 26 publications
(26 reference statements)
1
106
0
1
Order By: Relevance
“…Phase I studies by our group [6] and Meredith et al [7,8] have shown its feasibility and safety in human subjects. However, because minimal residual disease is an infraclinical condition, some assumed already-cured patients should be considered part of the target group.…”
Section: Introductionmentioning
confidence: 99%
“…Phase I studies by our group [6] and Meredith et al [7,8] have shown its feasibility and safety in human subjects. However, because minimal residual disease is an infraclinical condition, some assumed already-cured patients should be considered part of the target group.…”
Section: Introductionmentioning
confidence: 99%
“…The independent review shows more early patients with progression than previously noted when pretreatment and posttreatment comparison used the product of index lesion diameter (Table 2). 17,37 However, the later independent review did not necessarily use the same index lesions, which contributed to less than complete concordance of tumor growth results from those previously reported 17. Although the optimal tumor efficacy with α-emitters is proposed to be for microscopic disease, regression was noted among various sized gross lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Radioactive tracer metals, such as 99m Tc, 55 Co, 64/67 Cu, or 212 Pb, also can be incorporated into the tag (manuscripts in preparation), and these isotopes have proven utility in diagnostic imaging. 48−54 As shown here, Ni(II) can be selectively inserted into the tag even when placed in a protein sequence, and though not currently in wide usage, 57 Ni could be substituted and monitored based on its positron or X-ray emission. 55,56 Ni- cla MP has been shown to act as catalytic antioxidant, 1921 and the Ni- cla MP complex retains that activity in the context of a protein system.…”
Section: Discussionmentioning
confidence: 99%